Der Referentenentwurf des Raumordnungsgesetzes 2008: Inhalte und erste Einschätzungen - Müller, Christian (Raumforschung und Raumordnung | Spatial Research and Planning, 2008)
The Federal Ministry of Transport, Building and Urban Affairs presented a first draft of the new Regional Planning Act. The draft adopts the well-established mechanisms and instruments of the actual legislation and enhances them. It intends to provide a full federal regulation of regional planning, at the same time the draft aims to leave scope for the Bundesländer.